Permanent education to promote pediatric patient safety: an integrative review (Research, Society and Development, 2020)
This article aims to investigate the scientific production about the use of permanent education to promote the safety of pediatric patients. It is an integrative review of articles from the ADOLEC, LILACS, BDENF and SciELO and PubMed databases published between 2015 and 2019. Permanent Health Education (EPS) is a strategy that incorporates new reflections in the work environment and is based on meaningful learning to transform professional practices. Considering that the occurrence of adverse events in health care is a worldwide concern, the expansion of actions, such as the introduction of educational strategies in the professional environment, can be an important measure to promote child safety. Regarding the results, 04 studies met the inclusion criteria of the research emerging as empirical categories: Approaches to Pediatric Patient Safety and contributions of Permanent Education in favor of Pediatric Patient Safety. It was concluded that EPS, through the use of active learning methodologies, can sensitize professionals to safe practices in favor of the child, however, studies on this theme are still scarce.